Effect of Foreign Labour Migration on their Spouse - Mishra, Manamaya; Khadka, Bimal Kumar; Sijapati, Dipendra Bikram; Bhattari, Srijan (Nepal Population Journal, 2026)
This paper focuses on the impact of foreign labor migration on their spouse to understand the economic, social, and demographic effects on the left behind family members, especially spouses in Ward No. 5, Bhardeu of Konjyosom Rural Municipality of Lalitpur district. 150 respondents, mostly spouses, provided quantitative data that was gathered using a structured questionnaire and planned interviews utilizing the census approach. Most migrants are Tamang men who are driven to relocate overseas by social and economic pressures. Malaysia is the prime country of destination for foreign labour migrants with more than half (56%) having migrated there an increase in workload and experiences of social discrimination among female spouses and decrease in communication among married spouses illustrate some social and demographic challenges associated with foreign labour migration on the left behind spouses. According to this study, left-behind spouses feel more at ease discussing the social discrimination they encounter with their family members rather than with other community members and institutions. This demonstrates how information about such situations may be limited to the migrant’s home. These repercussions are varied, and to balance them, extensive government regulations that cater to the demands are required, as are support services for spouses who have been left behind. To eliminate unfavorable misconceptions about overseas labor migration and educate the public about the difficulties experienced by left-behind spouses, community awareness is essential.